2005
DOI: 10.5713/ajas.2006.160
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Genetic Correlations between Production and Semen Traits in Boar

Abstract: Currently, boars selected for commercial use as AI sires are evaluated on grow-finish performance and carcass characteristics. If AI sires were also evaluated and selected on semen production, it may be possible to reduce the number of boars required to service sows, thereby improving the productivity and profitability of the boar stud. The objective of this study was to estimate genetic correlations between production and semen traits in the boar: average daily gain (ADG), backfat thickness (BF) and muscle de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 15 publications
10
31
0
1
Order By: Relevance
“…The advantage of using average values is a simplification of the numerical procedures. According to Oh et al (2006), the heritabilities calculated for the average values of semen traits are identical to the repeatabilities for semen traits defined per collection, since permanent environmental effects were not separated in the model when using average values. Probably it would be more proper to replace 'identical' by 'similar'.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The advantage of using average values is a simplification of the numerical procedures. According to Oh et al (2006), the heritabilities calculated for the average values of semen traits are identical to the repeatabilities for semen traits defined per collection, since permanent environmental effects were not separated in the model when using average values. Probably it would be more proper to replace 'identical' by 'similar'.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is difficult to draw unambiguous conclusions from these results. Oh et al (2006) found that genetic correlations between average daily gain and semen traits were generally low and not different from zero and that genetic correlations between backfat thickness and semen traits (semen volume, sperm concentration, total number of spermatozoa and number of extended doses) were positive in sign; therefore, selection against backfat thickness (for high lean meat content) would have a negative effect on semen traits. The latter authors admit that the estimates of genetic correlations may be biased due to the inability to properly account for the boar's permanent environmental effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations